2002
DOI: 10.1002/glia.10180
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1‐phosphate induces the production of glial cell line‐derived neurotrophic factor and cellular proliferation in astrocytes

Abstract: Sphingosine 1-phosphate (S1P) is a platelet-derived bioactive sphingolipid that evokes a variety of biological responses. To understand the role of S1P in the central nervous system, we have examined the effect of S1P on the production of glial cell line-derived neurotrophic factor (GDNF) and growth regulation of cortical astrocytes from rat embryo. Moreover, we examined the possibility that the expression of GDNF is regulated differently in cultured astrocytes from the stroke-prone spontaneously hypertensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 41 publications
0
46
1
Order By: Relevance
“…Whether treatment with S1P receptor modulators in MS would enhance or attenuate OLG regeneration and remyelination may depend not only on the concentrations reached in brain tissues, but also on the summation of their effects on all CNS cell types. S1P has been reported to induce proliferation of astrocytes and neural progenitor cells, though the S1P receptor subtype involved was not determined in these studies (Bassi et al, 2006;Harada et al, 2004;Pebay et al, 2001;Yamagata et al, 2003). S1P also stimulates the production of glial cell line-derived neurotrophic factor in astrocytes Yamagata et al, 2003), which can enhance PNS myelination, as observed in our Schwann cell-neuron coculture studies (Iwase et al, 2005).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Whether treatment with S1P receptor modulators in MS would enhance or attenuate OLG regeneration and remyelination may depend not only on the concentrations reached in brain tissues, but also on the summation of their effects on all CNS cell types. S1P has been reported to induce proliferation of astrocytes and neural progenitor cells, though the S1P receptor subtype involved was not determined in these studies (Bassi et al, 2006;Harada et al, 2004;Pebay et al, 2001;Yamagata et al, 2003). S1P also stimulates the production of glial cell line-derived neurotrophic factor in astrocytes Yamagata et al, 2003), which can enhance PNS myelination, as observed in our Schwann cell-neuron coculture studies (Iwase et al, 2005).…”
Section: Discussionmentioning
confidence: 74%
“…S1P has been reported to induce proliferation of astrocytes and neural progenitor cells, though the S1P receptor subtype involved was not determined in these studies (Bassi et al, 2006;Harada et al, 2004;Pebay et al, 2001;Yamagata et al, 2003). S1P also stimulates the production of glial cell line-derived neurotrophic factor in astrocytes Yamagata et al, 2003), which can enhance PNS myelination, as observed in our Schwann cell-neuron coculture studies (Iwase et al, 2005). Furthermore, S1P signaling in OLG lineage cells is likely to be regulated by growth factors, and vice versa, as demonstrated with PDGF in this study.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, studies with pharmacological inhibitors suggest that activation of Rho pathways also plays a role in regulating proliferative responses for all three receptor classes that is independent of MAPK signaling cascades. Whereas previous reports have described varying aspects of PAR-or LPL-receptor mediated effects on astrocyte proliferation in vitro (Keller et al, 1997;Ramakers and Moolenaar, 1998;Tabuchi et al, 2000;Pebay et al, 2001;Steiner et al, 2002;Wang et al, 2002a;Yamagata et al, 2003), in this study we have sought to link in vivo effects of PAR-1, LPA, and S1P on reactive astrogliosis with shared signaling pathways for these receptors that mediate proliferative responses in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…LPA is abundant in rat brain (Das and Hajra, 1989), and physiologically active concentrations of LPA have been detected in cerebrospinal fluid in an experimental model of hemorrhagic injury (Tigyi et al, 1995). LPA and S1P have been shown to induce proliferation of astrocytes in culture (Keller et al, 1997;Ramakers and Moolenaar, 1998;Tabuchi et al, 2000;Pebay et al, 2001;Steiner et al, 2002;Yamagata et al, 2003), although some reports indicate that LPA is not a mitogen for astrocytes (Tigyi et al, 1994;Fuentes et al, 1999;Pebay et al, 1999).…”
Section: R-(ϩ)-trans-n-(4-pyridyl)-4-(1-aminoethyl)-cyclohexanementioning
confidence: 99%
“…S1PRs are widely expressed in the central nervous system (CNS), with region-specific distributions (Toman and Spiegel 2002;Jaillard et al 2005;Ohuchi et al 2008;Chun and Hartung 2010). The S1P/S1PR signal has been shown to play an important role in neural development, regulation of neural stem cells and glial migration, astrocyte proliferation, protection against apoptosis, and, more recently, modulation of neuronal excitability and glutamatergic neurotransmission (Chun et al 2000;Toman and Spiegel 2002;Yamagata et al 2003;Harada et al 2004;Kajimoto et al 2007;Kimura et al 2007;Milstien et al 2007;Ohuchi et al 2008). However, in situ localization of S1PRs in the human CNS remains unclear because of the lack of specific antibodies against S1PRs; most findings have been obtained from experiments at the mRNA level (Brinkmann 2009).…”
Section: Introductionmentioning
confidence: 99%